Hubungan Pengetahuan Ibu Dengan Minat Terhadap Senam Nifas - Umi Fania Julianti; Emiliana Nurri Astuti (JUKEJ : Jurnal Kesehatan Jompa, 2022)
Postpartum gymnastics is one of the needs of postpartum mothers, it is very important to do it during the postpartum period as an effort to accelerate the recovery of maternal health. Postpartum gymnastics can be done by mothers knowing the benefits of postpartum exercises, so it is very necessary to encourage mothers' interest in doing postpartum exercises and having good knowledge so that mothers' interest in postpartum exercises is high so that they can be carried out continuously. The purpose of this study was to determine the relationship between mother's knowledge and interest in postpartum exercise. This research method uses an analytic survey research with a cross sectional approach. This research was conducted at PMB Endang Sulastri, Singkawang City from September to November 2022. The population of this study was all postpartum mothers who were treated at PMB Endang Sulastri, totaling 67 people. The research sample consisted of 30 postpartum mothers who were treated at PMB using accidental sampling technique. Collecting research data using a questionnaire. Bivariate data analysis using Spearman rank test. The conclusion of this study is that there is a relationship between maternal knowledge and interest in postpartum exercise with the Spearman Rank test results obtained a significance of 0.000 (α < 0.05), the Coefficient Correlation value of 0.771 which indicates a very strong relationship strength.